Travelling in New Formes: Reissued and Reprinted Travel Literature in the Long Eighteenth Century - Day, Matthew (Mémoires du livre / Studies in Book Culture, 2013)
Despite increased recognition of the importance of the material nature of the book to our understanding of the creation of meanings, there has been relatively little focus on the travel literature of the eighteenth century. The market was enormous and a significant part of it comprised reissued and reprinted works. This article looks at the way books that returned to the market were given new contexts and created new meanings without changing the language of the main body of the text. By careful consideration of paratextual features such as title-pages, dedicatory epistles, marginalia and running titles and by considering such issues as the gathering of texts into collections, this article demonstrates the financial, political and ideological motives behind the reissue and reprinting of books. It shows how, through them, texts were 'reformed' in many different ways and suggests that reissues and reprints created, in effect, new books.